Coping with Pregnancy in Academic Environment: Experiences of Pregnant Students in A Public University in Ghana - Araba Etuah Priscilla; Yao Gbagbo Fred; Nkrumah Jacqueline (Journal of Women's Reproductive Health, 2018)
Background: The Ghanaian culture expects women of reproductive age to reproduce. This makes pregnancy an acceptable occurrence in most tertiary institutions in Ghana. Although Ghanaian Universities allow pregnancy in school, challenges associated with pregnancies do not exempt pregnant students from following the academic requirements of the universities. This study therefore explores students’ experiences of copying with pregnancy in an academic environment in Ghana. Methods: This was a case study, quantitative and qualitative design using structured questionnaires and semi-structured interview guides respectively for data collection. Respondents comprised twenty (30) pregnant full time and part time female students from campuses of University of Education, Winneba. Data collection was between October 2016 and May 2017. Quantitative data were analysed using statistical package for social sciences (SPSS) version 23. The qualitative data was transcribed and manually analysed thematically. Results: The study found that majority of participants were adults between ages 26 and 30 years. More than half of them (66.7%) had no child and this was their first pregnancy which they felt was mistimed as it occurred during schooling, posing some physiological, financial and academic challenges which compelled students to devise various coping strategies to combine academic work and pregnancy amidst limited University provisions for pregnant students. Conclusions: The study results have policy and programme implications for meeting women’s needs for pursuing academic and reproductive goals concurrently. The study recommends that public universities in Ghana should institutionalise programmes on preconception counselling and coping with pregnancy in academic environment to enable female students make informed decisions on exercising their reproductive rights in whilst in the university to ensure positive maternal health outcomes.
Keywords: coping